Medium access control - physical cross-layer design. - Dimic, G. (IEEE Signal processing magazine)
This article reviewed the various aspects of MAC-PHY cross-layer designs, with the goals of introducing pertinent queuing and stability analysis tools to the SP-oriented readership, and illustrating the advantages of such cross-layer designs using the recently introduced class of xNDMA protocols as an example. The results of queuing analysis show that a jointly designed MAC-PHY layer provides increased throughput and low delay characteristics over a wide range of offered loads. The throughput-delay benefits of xNDMA come at the expense of a moderate increase in receiver complexity and power consumption.